An environmental index of noise and light pollution at EU by spatial correlation of quiet and unlit areas. (February 2017) - Votsi, Nefta-Eleftheria P.; Kallimanis, Athanasios S.; Pantis, Ioannis D.
Abstract: Quietness exists in places without human induced noise sources and could offer multiple benefits to citizens. Unlit areas are sites free of human intense interference at night time. The aim of this research is to develop an integrated environmental index of noise and light pollution. In order to achieve this goal the spatial pattern of quietness and darkness of Europe was identified, as well as their overlap. The environmental index revealed that the spatial patterns of Quiet and Unlit Areas differ to a great extent highlighting the importance of preserving quietness as well as darkness in EU. The spatial overlap of these two environmental characteristics covers 32.06% of EU surface area, which could be considered a feasible threshold for protection. This diurnal and nocturnal metric of environmental quality accompanied with all direct and indirect benefits to human well-being could indicate a target for environmental protection in the EU policy and practices. Graphical abstract: Highlights: An environmental diurnal and nocturnal metric in EU is proposed. The overlap of Quiet and Unlit Areas could indicate areas of environmental quality. The protection of Natural Quiet and Darkness may direct environmental policy. Abstract : An environmental metric in EU is proposed. Quiet and Unlit Areas could indicate areas of human sensory perception of environmental quality.